(untitled) (Medical Forum Monthly, 2020)
Objective: To quantify the effects of dissemination & implementation of updated guidelines to achieve reduction &promotion of judicious prescription of opioid analgesics. Study Design: Experimental descriptive study Place and Duration of Study: This study was conducted at Sheikh Khalifa Bin Zayad Alnayan Hospital (CMH) Rawalakot from January to October 2019. Materials and Methods: Summary of updated guidelines, agreed by a panel of experts,for opioid analgesic’s prescriptionwas circulated along with personal communications to 94practicing doctors; 42 General physicians,5 dental surgeons,42 specialists & 5 postgraduate trainees. They were requested to read and implement the guidelines. After few weeks to months; on second visit, feedback of effects of these guidelines was collected through a well-designed Performa. Results: Out of 94 doctors, 71 (75.5%) were male and 23 (24.5%) were female. Majority of doctors(94.68 %) doctors stated that their overall rate of opioid analgesic’s prescription has decreased; on average by51% with maximum 95% and minimum 10%.Knowledge about safe and effective opioid prescription has increased in 97.87%. Assessment of risk factors was started by 93.61 % and patient’s counseling by 88.29 % of doctors.Conclusion: Educating the practicing doctors about Updated Guidelines on opioid analgesic’s prescription has significantly reduced the opioid prescription rate along with improvement in its judicious prescription. It is an important step to prevent opioid and overuse.